Adaptação transcultural e propriedades de medida do Life-H 3.1-Brasil para avaliação da participação social em hemiparéticos - Fernanda Sabine Nunes de Assumpção (2014)
According to the World Health Organization, social participation refers to "The individualss engagement in life situations in relation to their health conditions, body functions and structures, activities and contextual factors." Stroke is the major cause of disability and may affect participation in meaningful occupations and life satisfaction. The LIFE-H 3.1 assesses social participation through questions reagrding performance or current activities, the type of required assistance, and the individuals satisfaction. The purpose of this study was to cross-culturally adapt this instrument to the Brazilian-Portuguese language and investigate its measurement properties. The LIFE-H 3.1 was translated and adapted to Portuguese-Brazil, following standardized procedures and was subjected to test-retest reliability analyses. The measurement properties of the adapted version were evaluated using Rasch analyses with 90 community-dwelling chronic stroke subjects. The LIFE-H 3.1- Brazil showed adequate test-retest reliability (ICC=0.74-0.98) and stability of both, item calibration (ICC=0.93) and subjectss measures (ICC=0.97). It allowed the discrimination of subjects into six levels of social participation and the items into eightl levels of difficulty. Of the 77 items, four (5.2%) did not fit into the statistical model. As expected, the analyses supported the multidimensional nature of instruments aimed to measure social participation and showed evidence of construct validity. However, the scoring criteria of the LIFE-H 3.1 were not always fully utilized, suggesting that they could be simplified. The findings provided evidence of the clinical applicability of the LIFE-H 3.1-Brazil with chronic stroke subjects, since it may be applied in individuals with various levels of social participation.